Optimal approach for building scheduling algorithm in satellite communication - M. Al-Saegh, Ali (International Journal of Engineering and Technology, 2018)
Building scheduling algorithms in satellite communication links became a necessity according to the typical problems that satellite networks suffers from, such as congestions, jamming, mobility, atmospheric impairment, and achieving the quality of service (QoS) requirements. However, building efficient algorithms needs several considerations that should be taken into account. Such as satellite and earth station node(s), link parameters and specifications, along with the service requirements and limitations. This paper presents efficient approach for accumulating the effective considerations that the designer should employ as a framework for building proper and efficient scheduling algorithm. The proposed approach provides proper solutions to the satellite communications impairments and satisfies the quality of service requirements in satellite communication networks.Â Â